A REVISION OF THE GENUS ARCHIDENDRON F. MUELL. (MIMOSACEAE) - DE WIT, H. C. D. (REINWARDTIA, 1952)
1. The present paper is the authors second revision of the genus Archidendron.The validity of the genus is briefly discussed.2. The genus has its centre of speciation in New Guinea. The number of speciestreated is 31, not counting a few insufficiently known species. A key is given to thespecies and varieties, which are described.3. The following are new species or varieties: Archidendron affine De Wit,A. calliandrum De Wit, A. dies-Christi De Wit, A. nervosum De Wit, A. parviflorumvar. longipes De Wit, and A. trifoliolatum De Wit.4. New combinations are: Archidendron gogolense (K. Schum. & Laut.) De Wit(basonym: Hansemannia gogolense K. Schum. & Laut.) and A.lucyi var. schleohterii(Harms) De Wit (basonym: Archidendron schlechterii Harms). .